Development of a Nomogram to Predict Disease-Specific Survival for Patients After Resection of a Non-Metastatic Adenocarcinoma of the Pancreatic Body and Tail - Zou, Yiping; Han, Hongwei; Ruan, Shiye; Jian, Zhixiang; Jin, Liang; Zhang, Yuanpeng; Chen, Zhihong; Yin, Zi; Ma, Zuyi; Jin, Haosheng; Dai, Menghua; Shi, Ning (Frontiers in Oncology, 2020)
Background: Models for predicting patient survival after resection of a non-metastatic adenocarcinoma of the pancreatic body and tail (APBT) are scarce. We wished to establish and validate a nomogram to predict disease-specific survival (DSS) of these patients. Methods: A total of 1435 patients screened from the Surveillance, Epidemiology, and End Results (SEER) database were included and divided randomly into a training set (TS; n = 1007) and internal-validation set (IVS; n = 428) at a ratio of 7:3. Cox-regression analyses were conducted to select independent predictors in the TS, and a nomogram was constructed. The model was subjected to the IVS and an external validation set (EVS) comprising 151 patients from two tertiary hospitals. Results: Five independent risk factors (age at the diagnosis, chemotherapy, tumor grade, T stage, and the lymph node radio) were identified and integrated into the nomogram. Calibration curves indicated that the nomogram could predict DSS at 1, 2 and 3 years accurately. The nomogram had a higher concordance index for predicting DSS compared with that using the 8th edition of American Joint Committee on Cancer (AJCC8) stage (TS: 0.681 vs. 0.606; IVS: 0.662 vs. 0.590; EVS: 0.675 vs. 0.608). The nomogram had better discrimination ability and clinical utility than the AJCC8 stage for predicting 1-, 2- and 3-year DSS. Conclusion: Our developed nomogram could accurately predict DSS in patients after resection of a non-metastatic APBT.